2019
DOI: 10.18805/lr-4147
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Profitability of Cereal-Legume Forages Vis-a-Vis Their Effect on Soil Nutrient Status in Indo-Gangetic Plains

Abstract: The present study was conducted to evaluation of production potential of different forage crops commonly gown by farmers. The experiment was carried out in randomized complete block design with eight treatments and three replications at research farm of Agronomy Section, ICAR-NDRI, Karnal (Haryana). Among eight treatments, two perennial forage crops napier bajra hybrid(NBH), guinea grass cultivated sole as well as intercropping with cowpea and four seasonal fodder crops (cowpea, sorghum, baby corn and maize) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The higher GFY of the component crops associated with perennial cropping systems resulted in higher DMY, even with considerable variation in dry matter concentration. Perennial intercropping systems such as Bajra-Napier hybrid + cowpea; guinea grass + cowpea [2]; and Bajra-Napier hybrid (BNH-10) + desmanthus at 1:5 row proportions produced higher GFY [21]. Increased DMY with Napier grass and herbaceous perennial legume intercropping systems were reported by Menbere et al [24] from research in Ethiopia.…”
Section: Biomass Yieldmentioning
confidence: 97%
See 2 more Smart Citations
“…The higher GFY of the component crops associated with perennial cropping systems resulted in higher DMY, even with considerable variation in dry matter concentration. Perennial intercropping systems such as Bajra-Napier hybrid + cowpea; guinea grass + cowpea [2]; and Bajra-Napier hybrid (BNH-10) + desmanthus at 1:5 row proportions produced higher GFY [21]. Increased DMY with Napier grass and herbaceous perennial legume intercropping systems were reported by Menbere et al [24] from research in Ethiopia.…”
Section: Biomass Yieldmentioning
confidence: 97%
“…According to the National Commission on Agriculture, the recommended area for animal feed (forage or fodder) production should be 10% of arable land i.e., 16.5 million hectares (m ha). This being said, the area under animal feed cultivation has decreased due to increased cultivation of food and commercial crops [2]. At present, only 8.6 m ha area is devoted to livestock feed production in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to incorporation of clusterbean with sorghum which helped in achieving nutrient economy. Surve et al (2012) and Hindoriya et al (2019) also reported similar finding in cereal and legume mixtures.…”
Section: Resultsmentioning
confidence: 53%
“…Since, cowpea green manure contains 0.7% N, 0.1-0.2% P 2 O 5 and 0.6% K 2 O, the incorporation of its residues increases the primary macronutrient content. It is capable for accumulation of 5-6 tonnes/ha of dry biomass (Hindoriya et al, 2019) and 100 kg N/ha in 50-60 days if it is well-managed. It has good root nodules and thus, supplies atmospheric N to available form in soil and improves the soil rhizosphere conditions.…”
Section: Introductionmentioning
confidence: 99%